2011
DOI: 10.4314/pamj.v8i1.71085
|View full text |Cite
|
Sign up to set email alerts
|

Nurses and challenges faced as clinical educators: a survey of a group of nurses in Cameroon

Abstract: BackgroundClinical teaching is an important component of clinical education. In nursing, clinical teaching is ensured by clinical nurse educators (CNEs). This study aimed at describing the major challenges faced by CNEs in Cameroon.MethodsIn a qualitative study, supplemented with quantitative methods, CNEs were enrolled from three health districts to represent their frequency in Cameroon’s health delivery system.ResultsA total of 56 CNEs participated in the study, of whom, as many as 58.9% acknowledged always … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 11 publications
(10 reference statements)
4
44
0
1
Order By: Relevance
“…Effective clinical teaching is critical for students' learning in the clinical setting [2,3]. This is because clinical teaching helps to prepare students for the work they will have to do as practicing nurses.…”
Section: Introductionmentioning
confidence: 99%
“…Effective clinical teaching is critical for students' learning in the clinical setting [2,3]. This is because clinical teaching helps to prepare students for the work they will have to do as practicing nurses.…”
Section: Introductionmentioning
confidence: 99%
“…[8,46,65] In reality many faculty and CIs learn on the job through experiential role performance, a finding implies that those who supervise and evaluate students may be insufficiently equipped for the role. [65] Difficulty balancing student learning with patient safety. Balancing complex patient needs with the learning needs of students is a major challenge for CIs.…”
Section: Challenges Associated With the Traditional Modelmentioning
confidence: 99%
“…These findings corroborate evidence in the literature that nursing students are often taught by clinicians who in most cases have limited or no prior formal teaching background. [8,45,65] It cannot be assumed that all clinically competent nurses can function effectively as clinical teachers. CIs must be well prepared with good nursing and teaching knowledge and experience.…”
Section: Challenges Associated With the Traditional Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…After interviewing clinical nurse teachers, Eta, Atanga, Atashili, and D'Cruz concluded that failing to prepare clinical teachers to teach students in practice could limit students' ability to meet their daily clinical goals. [3] Considering that the number of nursing students will continue to rise in SA due to the increasing demand for nursing care, it is essential to explore the experiences that CTs encounter at the beginning of their academic careers. Based on these data, strategies can then be developed that may help teachers become more effective in their new roles.…”
Section: Introductionmentioning
confidence: 99%